HISTORY OF HIGHLY PATHOGENIC AVIAN INFLUENZA ERADICATION IN RUSSIAN FEDERATION IN 2016–2017 - M. S. Volkov; V. N. Irza; A. V. Varkentin (Ветеринария сегодня)
Epidemic patterns of highly pathogenic avian influenza А/Н5N8 spread in the Russian Federation are demonstrated, history of the disease outbreak eradication in domestic poultry is described, basic reasons of the dangerous virus introduction on the commercial farms are analyzed and issues of the outbreak containment are highlighted. Specific properties of H5N8 disease progression and clinical manifestation are demonstrated against H5N1 disease. Data of epidemic investigations of the virus introduction to the closed-type farms are integrated. Basic attention is given to the destruction of poultry died and stamped out during implementation of anti-epidemic measures, and potential alternative ways of biological waste destruction are demonstrated. Principal risks of introduction of emerging influenza virus subtypes into the Russian Federation are determined. Further spread of avian influenza over the Russian territory is expected due to the current epidemic situation, the virus persistence in the vectors, maintenance of its viability in the environment and seasonal migrations of the wild birds.  Major threat of the agent introduction comes from the neighbouring East Asia and Far East countries (China, Japan, Korea). Herewith, introduction of potentially zoonotic viruses is also possible. Risk of the virus introduction from the European countries, Near East countries and Central Asia cannot be excluded. For now, drastic measures still remain the only tool for the disease control and the strategy of limited targeted AI vaccination in the backyards minimizes the virus introduction to the commercial farms located in the risk zones.